French Presence in Brazil in the Nineteenth Century: analysis of the accounting archives of Casa Boris’s in the period from 1872 to 1887 - Cosenza, José Paulo; De Rocchi, Carlos Antonio; Ribeiro, Carlos Alberto Campello (Review of Business Management, 2014)
Founded in Brazilian imperial period, Casa Boris had an important commercial role in the Northeast region of Brazil. Using a competitive business structure, it linked the Ceará Province (branch) with France (headquarters), by importing manufactured goods and exporting raw materials. In this paper, we studied the Journal and Ledger of Casa Boris, particularly from 1872 to 1887. The study aimed to analyze the contents of the accounting records contained in these books so as to report facts and points of historical interest to the Brazilian Accounting. The main contribution of the research, in general, is associated with an attempt to understand the influence of political, economic, social and institutional settings on accounting practices and vice-versa. Our findings led to the conclusion that the bookkeeping of Casa Boris was transparent to reveal the quality of accounting control of commercial operations undertaken by the firm and also shows the coexistence of a incipient provincial market that concomitantly linked Brazil to Europe in the second period of Brazilian Monarchical Empire.